2001
DOI: 10.1088/0953-8984/13/34/323
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic x-ray scattering at ultrahigh pressures

Abstract: Inelastic x-ray scattering (IXS) provides high-pressure research with an arsenal of analytical capabilities for key measurements that were previously unattainable, and high-pressure research provides IXS with numerous applications where the technique has unique advantages over other methods. High-pressure investigations can now be conducted using non-resonant IXS, resonant IXS, nuclear resonant IXS and x-ray emission spectroscopy with energy resolutions of 100 meV to 1 eV for electronic transitions and 1 to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 99 publications
1
28
0
Order By: Relevance
“…IXS measurements at high pressures provide valuable insight into the change of metallic behaviors, but are very challenging because the double-differential scattering cross-section (16) is very small and the background signals from the anvils and gasket can be overwhelming. Nevertheless, high-pressure IXS of body-centered cubic (bcc) Na has progressed steadily since a single q measurement at 1.3-fold densification (corresponding to 2.7 GPa) a decade ago (17). Very recently, Loa et al (18) reported multiple q measurements of bcc Na up to 2.6-fold densification (43 GPa), showed deviations from an FE metal, and conducted ab initio calculations to explain the deviation.…”
mentioning
confidence: 99%
“…IXS measurements at high pressures provide valuable insight into the change of metallic behaviors, but are very challenging because the double-differential scattering cross-section (16) is very small and the background signals from the anvils and gasket can be overwhelming. Nevertheless, high-pressure IXS of body-centered cubic (bcc) Na has progressed steadily since a single q measurement at 1.3-fold densification (corresponding to 2.7 GPa) a decade ago (17). Very recently, Loa et al (18) reported multiple q measurements of bcc Na up to 2.6-fold densification (43 GPa), showed deviations from an FE metal, and conducted ab initio calculations to explain the deviation.…”
mentioning
confidence: 99%
“…4 These high pressure states may be approached in the laboratory using either static or dynamic compression techniques. For static compressions, the instrument of choice is the diamond anvil cell (DAC) which allows access to pressures on the order of a few hundred GPa and temperatures of up to several thousand K. 5 In dynamic compression experiments the high pressure state is driven by a sudden impulse delivered by a high-power laser 6 or a variety of alternative means, including pulsed power facilities, 7-9 gas guns, 10,11 and high explosives. 12 With either approach, characterizing the material conditions is challenging because of the small sample size, limited access, and opacity.…”
Section: Introductionmentioning
confidence: 99%
“…8 Presently, HP-CAT has a spectrometer for the study of electronic excitations at low momentum transfer and core-electron excitations (Xray Raman scattering (XRS)) at larger scattering angle with ∼1 eV energy resolution. The spectrometer is designed to detect scattered photons of energies of interest with an energy resolution and momentum transfer corresponding to the physics process of interest.…”
Section: B High Pressure Inelastic X-ray Scatteringmentioning
confidence: 99%
“…4,5 Thanks to the continuous developments of extremely intense and focused Xray beams, together with the developments in high pressure vessels such as the X-ray transparent gasket and panoramic diamond anvil cells (DACs) with large opening angles, many X-ray spectroscopic methods (emission, inelastic scattering, nuclear resonant scattering (NRS), and magnetic circular dichroism) have become available for high pressure research since middle 1990s. [6][7][8][9][10] Since the beginning of user operation in 2002, the 16-ID-D beamline of the High Pressure Collaborative Access Team (HPCAT) at the Advanced Photon Source (APS) has been dedicated to high pressure spectroscopic studies, typically in DACs. 11 Current available techniques include X-ray emission spectroscopy (XES), inelastic X-ray scattering (IXS), and NRS.…”
Section: Introductionmentioning
confidence: 99%